Characterization and antiviral susceptibility of SARS-CoV-2 Omicron/BA.2 - Kawaoka, Yoshihiro; Uraki, Ryuta; Kiso, Maki; Iida, Shun; Imai, Masaki; Takashita, Emi; Kuroda, Makoto; Halfmann, Peter; Loeber, Samantha; Maemura, Tadashi; Yamayoshi, Seiya; Fujisaki, Seiichiro; et al. (Nature, 2022)
The recent emergence of SARS-CoV-2 Omicron variants possessing large numbers of mutations has raised concerns of decreased effectiveness of current vaccines, therapeutic monoclonal antibodies, and antiviral drugs for COVID-19 against these variants1,2. While the original Omicron lineage, BA.1, has become dominant in many countries, BA.2 has been detected in at least 67 countries and has become dominant in the Philippines, India, and Denmark. Here, we evaluated the replicative ability and pathogenicity of an authentic infectious BA.2 isolate in immunocompetent and human ACE2 (hACE2)-expressing mice and hamsters. In contrast to recent data with chimeric, recombinant SARS-CoV-2 strains expressing the spike proteins of BA.1 and BA.2 on an ancestral WK-521 backbone3, we observed similar infectivity and pathogenicity in mice and hamsters between BA.2 and BA.1, and less pathogenicity compared to early SARS-CoV-2 strains. We also observed a marked and significant reduction in the neutralizing activity of plasma from COVID-19 convalescent individuals and vaccine recipients against BA.2 compared to ancestral and Delta variant strains. In addition, we found that some therapeutic monoclonal antibodies (REGN10987/REGN10933, COV2-2196/COV2-2130, and S309) and antiviral drugs (molnupiravir, nirmatrelvir, and S-217622) can restrict viral infection in the respiratory organs of hamsters infected with BA.2. These findings suggest that the replication and pathogenicity of BA.2 is comparable to that of BA.1 in rodents and that several therapeutic monoclonal antibodies and antiviral compounds are effective against Omicron/BA.2 variants.